PENGARUH PENAMBAHAN GULA TERHADAP PRODUKTIVITAS ALKOHOL DALAM PEMBUATAN WINE BERBAHAN APEL BUANG (REJECT) DENGAN MENGGUNAKAN NOPKOR MZ.11 - Hermawan Dwi Ariyanto; Furqon Hidayatulloh; Joko Murwono (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Apple is one of a highly perishable fruit. Many apples fall down from the tree prematurely and known as an apple waste reject. A utilization of apple reject has not been yet developed. Beverage product processed from apples reject is an appropriate means to increase productivity and economic standards for the apple growers. It can be a solution to the decline in the price of apples at harvest time. Sugar content in apples varies depending on weather conditions, cultivation, and cultivation technology used. In general, an apple reject has a very low sugar contents ranging from 2% - 5%. One of the diversification products from apple reject is wine. Wine is one of an alcoholic beverages containing 8-15% alcohol made from fermented grape juice or other fruit. 14% of glucose content is a pre requirement of the fruit which may possible to be converted into alcohol. The aim of this study is to determine the effect of glucose content and the use of Nopkor MZ.11 on apple reject wine production. The addition of glucose concentration is necessary for the fermentation process with a variable of 10% w/v, 15% w/v, 20% w/v. The process of fermentation is performed in anaerobic conditions and a temperature of 30 ° C  for 8 days fermentation period and then the aging process are performed. Based on the result collected during the experiment, it was obtained that 15 % w/v is possibly to produce an alcohol content of 9.3 % in concentrations when the residual sugar found in wine was 5.8%.